Polymorphisms at the Microseminoprotein-beta locus associated with physiologic variation in beta-microseminoprotein and prostate-specific antigen levels. - Xu, X; Valtonen-André, C; Sävblom, C; Halldén, C; Lilja, H; Klein, R (2010)
BACKGROUND: rs10993994, a single nucleotide polymorphism (SNP) at the genetic locus encoding beta-microseminoprotein (beta-MSP), is associated with both prostate cancer risk and levels of blood prostate-specific antigen (PSA), a biomarker used in prostate cancer screening. Therefore, we wished to determine the association between SNPs at MSMB, the gene encoding beta-MSP, and the levels of prostate-produced biomarkers beta-MSP, PSA, and human kallikrein 2 (hK2) in blood and semen. METHODS: Blood and semen from 304 healthy young Swedish men (ages 18-21) were assayed for beta-MSP, PSA, and hK2. SNPs around MSMB were genotyped from matched DNA and analyzed for quantitative association with biomarker levels. Empirical P values were multiple test-corrected and the independence of each SNP's effect was determined. RESULTS: rs10993994 was significantly associated with the blood and semen levels of beta-MSP (both P < 1.0 x 10(-7)) and PSA (P = 0.00014 and P = 0.0019), and semen levels of hK2 (P = 0.00027). Additional copies of the prostate cancer risk allele resulted in lower beta-MSP but higher PSA levels, and singly explained 23% and 5% of the variation seen in semen beta-MSP and PSA, respectively. Additional SNPs at MSMB are associated with beta-MSP and PSA independently of rs10993994. CONCLUSIONS: SNPs at MSMB correlate with physiologic variation in beta-MSP and PSA levels in the blood and semen of healthy young Swedish men. In particular, rs10993994 has a strong effect on beta-MSP levels. IMPACT: Our results suggest a mechanism by which rs10993994 might predispose to prostate cancer and raise the possibility that genetic variation might need to be considered in interpreting the levels of these biomarkers.